Fahrstrategien zur Unfallvermeidung im Straßenverkehr für Einzel- und Mehrobjektszenarien - Schmidt, Christian (Schriftenreihe / Institut für Mess- und Regelungstechnik, Karlsruher Institut für Technologie, 2013)
The subject of this work is the determination of collision-free driving strategies. Firstly, the last possible maneuver is derived for a single object on the basis of reachable existence circles and is extended to a complete evasive maneuvre. Subsequently, the consideration is extended onto multiple objects. By the use of existence regions and kinematic configurations collision-free trajectories are determined and evaluated.